Vaginal leiomyoma: a common disease with a rare presentation - Ribeiro,Vânia Costa (2017)
Leiomyomas are pelvic smooth muscle tumours that present with a variety of clinical symptoms depending on site location. Although leiomyomas can be present in the uterus, round ligament, peritoneum and blood vessels, vaginal occurrence is a rare finding. This report describes a patient with a vaginal leiomyoma in the posterior wall of the vagina with complaints of abundant vaginal discharge and pelvic pain. Transvaginal excision of the tumour was performed with histopathologic diagnose and complete cure of the patient